APLICAÇÃO DA METODOLOGIA FMEA NA CRIAÇÃO DE UM BANCO DE DADOS DE OCORRÊNCIAS PÓS-OBRA COMO FERRAMENTA DE RETROALIMENTAÇÃO - Chagas, Felipe Cassiano F.; Santana, Wylliam B.; Maues, Luiz M. F.; Oliveira, Fabriccio de A. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The change of necessities and expectations from customers and the increasing market competitiveness induce companies to continuously improve their products and processes. Two main steps towards that are standardizing procedures and obtaining data feedback. However, in order for such feedback to effectively exist, it is necessary to create a database and to use information systems capable of storing, processing and distributing the collected data, to transform it into useful information. This way, this study defines as main goals the standardization of procedures and of information flow, the mapping of post-construction events and the proposal of a feedback tool; everything focused in a medium-sized construction company in the city of Belém (PA). The aforementioned tool is a database based on the FMEA (Failure Mode and Effect Analysis) methodology capable of organizing postconstruction events within a given hierarchy, identifying those whose problem results more important. Besides, it identifies the causes and the consequences of such problem. The results gathered so far are satisfactory, given that they helped the company's managers to identify the most impacting systems for processing data and planning new strategies to improve future projects.